2010
DOI: 10.1161/circoutcomes.110.949800
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Perspectives of a Multifaceted Intervention With a Focus on Technology

Abstract: Background-Few studies have investigated the effectiveness of multifaceted interventions from the study participants' perspective. We conducted qualitative interviews to understand patients' experiences with a multifaceted blood pressure (BP) control intervention involving interactive voice response technology, home BP monitoring, and pharmacist-led BP management. In the randomized study, the intervention resulted in clinically significant decreases in BP. Methods and Results-We used insights generated from in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…In the US study, issues with poor literacy were identified,28 whereas, although the population for the trial which underpinned this study16 was drawn from across the spectrum of social privilege and deprivation in Scotland, this was not a concern raised at any point. In some of the trials of larger interventions incorporating BP telemonitoring,12 17 18 it is hard to unravel the impact of the telemonitoring from the impact of the rest of the intervention. This study, and the trial outcome, suggests that the telemonitoring itself can overcome some of the barriers to an improved BP control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the US study, issues with poor literacy were identified,28 whereas, although the population for the trial which underpinned this study16 was drawn from across the spectrum of social privilege and deprivation in Scotland, this was not a concern raised at any point. In some of the trials of larger interventions incorporating BP telemonitoring,12 17 18 it is hard to unravel the impact of the telemonitoring from the impact of the rest of the intervention. This study, and the trial outcome, suggests that the telemonitoring itself can overcome some of the barriers to an improved BP control.…”
Section: Discussionmentioning
confidence: 99%
“…This study, and the trial outcome, suggests that the telemonitoring itself can overcome some of the barriers to an improved BP control. The added value of the additional interventions such as pharmacist support12 or medication self-management plans17 needs to be determined. Interestingly, the qualitative study associated with a trial which included telemonitoring and medication self-management suggested that although many participants would be happy to continue with the telemonitoring, few would be happy to continue with the medication self-management plans 13…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following removal of duplicates and title and abstract screening, 45 full text articles were assessed and 12 articles met the selection criteria [15][16][17][18][19][20][21][22][23][24][25][26]. (PRISMA diagram, Fig.…”
Section: Searchesmentioning
confidence: 99%
“…Examples include articles that report on randomized trials, 1,2 cross-sectional studies, 3 observational cohort studies, 4 economic analyses, 5-7 meta-analyses, 8 systematic reviews, 9,10 prepost designs, 11 simulations, 12 and qualitative research. 13,14 A glance at this content quickly dispels the myth that outcomes research is primarily associated with secondary data analyses and data mining. That type of work, for the appropriate questions and with the appropriate methodological approach, can make important contributions, but is hardly the only study design used by the field.…”
mentioning
confidence: 99%